Имитационная модель самоорганизации беспроводных сенсорных сетей - Теплицкая, С. Н.; Хуссейн, Я. Т. (ХНУРЭ, 2011)
The imitating model of self-organizing of wireless sensory networks is offered. Distinctive feature of algorithm is use of accommodation of sensor controls, power stock in the sensory node, level of a ratio signal/noise. The qualitative and quantitative analysis of efficiency of functioning of the offered algorithm is carried out.
Keywords: Сенсорная сеть; мониторинга различных ситуаций